Organic cultivation of onion under castor cake fertilization and irrigation depths - Gabriel Alves Botelho de Mello; Daniel Fonseca de Carvalho; Leonardo Oliveira Medici; Aldir Carlos Silva; Daniela Pinto Gomes; Marinaldo Ferreira Pinto (Acta Scientiarum. Agronomy, 2018)
Two experiments were carried out to evaluate the effects that different doses of castor bean (0, 200, and 300 g m-2) and irrigation levels (204, 224, 278, and 321 mm in 2014, and 278, 302, 397, and 444 mm in 2015) have on both the productivity and quality of onion bulbs. In the experiments, the experimental design was randomized blocks (4 x 3 factorial scheme), with five replicates. Irrigation management was performed using a Simplified Irrigation Device (SID) in response to soil water tension in the treatment of highest irrigation depth. The following variables were evaluated: plant dry biomass (PDB), bulb dry biomass (BDB), total yield (TY), mean bulb fresh weight (MBFW), mean bulb dry weight (MBDW), mean bulb diameter (MBD) and water use efficiency (WUE). The highest irrigation depths positively influenced the mean production of onion bulbs, regardless of the applied dose of castor cake. The doses of castor cake positively influenced the production of onion bulbs when higher irrigation depths were applied.